2020
DOI: 10.3897/phytokeys.161.51046
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis of karyotype similarity coefficients in Epimedium (Berberidaceae): insights in the systematics and evolution

Abstract: In order to evaluate the genome evolution and systematics, karyotype analysis of mitotic metaphase chromosomes in 51 taxa of Epimedium and two species of Vancouveria was conducted. The 53 taxa were clustered, based on their karyotype similarity coefficients. Results showed that the 53 taxa studied were all diploid with 12 chromosomes (2n = 2x = 12). Each taxon had one pair of satellites located on pair I of homologous chromosomes. Moreover, the karyotype types of the 53 taxa studied were all type 1A or 2A of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In the Northern Hemisphere, Berberidaceae exhibits seven intercontinental disjunctions: the East Asian (EA) and western North American (WNA) disjunctions in Achlys (Fukuda, 1967) and Mahonia (Yu and Chung, 2017;Chen et al, 2020), the Eurasian Epimedium and its WNA disjunct sister genus Vancouveria (Stearn, 1938;Zhang et al, 2007), the EA and eastern North American (ENA) disjunctions in Diphylleia (Ying et al, 1984) and Caulophyllum (Loconte and Blackwell, 1985), and the EA monotypic genera Sinopodophyllum (Ying, 1979) and Plagiorhegma (Hutchinson, 1920) and their respective disjunct ENA sister genera Podophyllum and Jeffersonia (Wang et al, 2007). Because of great economic, ecological, and taxonomic interests, Berberidaceae has been studied extensively in seedling morphology (Terabayashi, 1985c), floral morphology (Terabayashi, 1985a;Brückner, 2000), embryology (Sastri, 1969), serology (Jensen, 1973), palynology (Zhang et al, 2017), wood anatomy (Carlquist, 1995), and chromosome cytology (Kuroki, 1970;Adhikari et al, 2014;Huang et al, 2018;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the Northern Hemisphere, Berberidaceae exhibits seven intercontinental disjunctions: the East Asian (EA) and western North American (WNA) disjunctions in Achlys (Fukuda, 1967) and Mahonia (Yu and Chung, 2017;Chen et al, 2020), the Eurasian Epimedium and its WNA disjunct sister genus Vancouveria (Stearn, 1938;Zhang et al, 2007), the EA and eastern North American (ENA) disjunctions in Diphylleia (Ying et al, 1984) and Caulophyllum (Loconte and Blackwell, 1985), and the EA monotypic genera Sinopodophyllum (Ying, 1979) and Plagiorhegma (Hutchinson, 1920) and their respective disjunct ENA sister genera Podophyllum and Jeffersonia (Wang et al, 2007). Because of great economic, ecological, and taxonomic interests, Berberidaceae has been studied extensively in seedling morphology (Terabayashi, 1985c), floral morphology (Terabayashi, 1985a;Brückner, 2000), embryology (Sastri, 1969), serology (Jensen, 1973), palynology (Zhang et al, 2017), wood anatomy (Carlquist, 1995), and chromosome cytology (Kuroki, 1970;Adhikari et al, 2014;Huang et al, 2018;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, there is a large discrepancy between the limited number of chromosomes and the large genome size of Epimedium species ( Chen et al., 2012 ; Liu et al., 2013 ; Wang et al., 2020 ). The E. pubescens genome is consisted of 66.94% of repetitive elements, which is much higher than other species from Ranunculales.…”
Section: Discussionmentioning
confidence: 99%
“…E. pubescens is an important species of Epimedium with high and stable level of 8-prenylated flavonoids as a major commercial source for Herba Epimedii (Chinese Pharmacopoeia Commission, 2020). In addition, E. pubescens as a diploid species (2n=2x=12), possesses the chromosomal structure of karyotype symmetry type of 2A, which is previously reported to be similar to most Epimedium species (Table S1) (Zhang et al, 2018;Wang et al, 2020). Therefore, E. pubescens is a suitable representative species for constructing the reference genome of Epimedium for answering evolutionary questions and the exploring biosynthetic mechanisms of medicinal compounds in Herba Epimedii.…”
Section: Introductionmentioning
confidence: 86%
“…The quality control of Yinyanghuo should focus on the problems of multiple provenances, multiple origins and difficult identification [64] . Epimedium is challenging taxon, with large intraspecific variations and unclear interspecific boundaries [66–71] . The highly similar morphological characteristics in Epimedium species often lead to the misuse in the medicinal market and threaten the efficiency and safety of the resulting herbal medicine [6,64] .…”
Section: Introductionmentioning
confidence: 99%
“…[64] Epimedium is challenging taxon, with large intraspecific variations and unclear interspecific boundaries. [66][67][68][69][70][71] The highly similar morphological characteristics in Epimedium species often lead to the misuse in the medicinal market and threaten the efficiency and safety of the resulting herbal medicine. [6,64] When the type specimens of E. wushanense were examined, it was found that they actually belonged three species, E. wushanense, E. ilicifolium Stearn and E. jinchengshanense Y. J. Zhang & J. Q. Li, which are highly similar in morphological characteristics.…”
Section: Introductionmentioning
confidence: 99%